Estudo do metabolismo oxidativo eritrocitário em ovinos anêmicos e portadores de parasitose gastrointestinal - Silva, Andreza Amaral da; Ferreira, Danilo Otávio Laurenti [UNESP]; Abreu, Fernanda Martins de [UNESP]; Dias, Adriano [UNESP]; Damasceno, Débora Cristina [UNESP]; Chiacchio, Simone Biagio [UNESP]; Gonçalves, Roberto Calderon [UNESP] (My University, 2012)
We evaluated the effect of anemia by chronic blood loss on the oxidative metabolism of erythrocytes of anemic (n=20) and non-anemic (n=10) sheep affected by gastrointestinal parasites. Samples of blood from the jugular vein (10 ml) were collected in tubes containing heparin and tubes containing EDTA (5 ml each) to the indirect determination of biomarkers of oxidative metabolism, superoxide Dismutase (SOD), Glutathione Peroxidase (GSH-Px), Glutathione (GSH-t); Thiobarbituric acid reactive substances (TBARS) and eritrocitárias determinations (packed cell volume, total count of red blood cells and hemoglobin), respectively. There was a statistically significant reduction in red blood cell count (p=0.02), hemoglobin (p=0.03) and packed cell volume (p<0.001) and elevation of the enzymatic activity of GSH-Px (p=0.016) in the erythrocytes of anemic animals. Anemia of chronic blood loss in sheep affected by gastrointestinal parasites, although inducing changes in oxidative metabolism, does not cause oxidative stress, as measured by determining the enzymatic activities of SOD and GSH-Px and the concentrations of TBARS and GSH-t.

Avaliou-se o efeito da anemia por perda crônica de sangue sobre o metabolismo oxidativo dos eritrócitos de ovinos anêmicos (n=20) e não anêmicos (n=10) acometidos por parasitose grastrointestinal. Amostras de sangue da veia jugular (10ml) foram colhidas em tubos contendo heparina e em tubos contendo EDTA (5mL cada) para a determinação indireta dos biomarcadores do metabolismo oxidativo [Superóxido Dismutase (SOD), Glutationa Peroxidase (GSH-Px), Glutationa Total (GSH-t); Substâncias Reativas ao Ácido Tiobarbitúrico (TBARS)] e das determinações eritrocitárias (volume globular, contagem total de hemácias e hemoglobina), respectivamente. Houve redução estatisticamente significativa da contagem total de hemácias (p=0,02), hemoglobina (p=0,03) e volume globular (p<0,001), além de elevação da atividade enzimática da GSH-Px (p=0,016) nos eritrócitos dos animais anêmicos. A anemia por perda crônica de sangue em ovinos com parasitose gastrointestinal, apesar de induzir alterações no metabolismo oxidativo, não provoca estresse oxidativo eritrocitário, medido por determinação das atividades enzimáticas da SOD e GSH-Px e das concentrações de GSH-t e TBARS.
Study of oxidative metabolism in sheep within anemic and with gastrointestinal parasite
Keywords: Oxidative stress; Anemia; Sheep; Estresse oxidativo; Anemia; Ovino